Energy Metabolism in Exercise-Induced Physiologic Cardiac Hypertrophy - Xiang, Kefa; Qin, Zhen; Zhang, Huimin; Liu, Xia (Frontiers in Pharmacology, 2020)
Physiologic hypertrophy of the heart preserves or enhances systolic function without interstitial fibrosis or cell death. As a unique form of physiological stress, regular exercise training can trigger the adaptation of cardiac muscle to cause physiological hypertrophy, partly due to its ability to improve cardiac metabolism. In heart failure (HF), cardiac dysfunction is closely associated with early initiation of maladaptive metabolic remodeling. A large amount of clinical and experimental evidence shows that metabolic homeostasis plays an important role in exercise training, which is conducive to the treatment and recovery of cardiovascular diseases. Potential mechanistic targets for modulation of cardiac metabolism have become a hot topic at present. Thus, exploring the energy metabolism mechanism in exercise-induced physiologic cardiac hypertrophy may produce new therapeutic targets, which will be helpful to design novel effective strategies. In this review, we summarize the changes of myocardial metabolism (fatty acid metabolism, carbohydrate metabolism, and mitochondrial adaptation), metabolically-related signaling molecules and probable regulatory mechanism of energy metabolism during exercise-induced physiological cardiac hypertrophy.